Cancer Cell Plasticity: Rapid Reversal of Chemosensitivity and Expression of Stemness Markers in Lung and Breast Cancer Tumorspheres. Issue 9 (31st March 2017) - Yakisich, Juan Sebastian; Azad, Neelam; Kaushik, Vivek; Iyer, Anand Krishnan V.
Abstract : In cancer cells, the reversible nature of the stemness status in terms of chemoresistance has been poorly characterized. In this study, we have simulated one cycle of environmental conditions to study such reversibility by first generating floating tumorspheres (FTs) from lung and breast cancer cells by culturing them in serum‐free media without the addition of any external mitogenic stimulation, and subsequently (after 2 weeks) re‐incubating them back in serum‐containing media to simulate routine culture conditions (RCCs). We found that cancer cells are extremely plastic: cells grown under RCCs become multidrug‐resistant when grown as FTs, but upon re‐incubation under RCCs quickly re‐attach and lose the acquired resistance. These phenotypic changes are accompanied by concomitant changes in the expression of key proteins associated with multiple pathways important for chemoresistance, survival, and stemness maintenance. Therefore, our strategy provides an excellent experimental model to study environmental factors that modulate the plasticity of cancer cells. J. Cell. Physiol. 232: 2280–2286, 2017. © 2016 Wiley Periodicals, Inc. Abstract : In this report, we have developed a protocol to grow lung and breast cancer cells as floating tumorspheres (FTs) in the absence of any external mitogenic stimulation. By using routine culture conditions (RCCs), FTs, and revertant cells (FTs cell that reattach when incubated back under RCCs), we simulated one cycle of environmental conditions in order to study the plasticity of cancer cells. We found that cancer cells are extremely plastic: cells grown under RCCs become multidrug‐resistant, when grown as FTs but upon re‐incubation under RCCs quickly re‐attach and lose the acquired resistance. These phenotypic changes are accompanied by concomitant changes in the expression of key proteins associated with multiple pathways important for chemoresistance, survival, and stemness maintenance.